The Watsons go to Birmingham--1963 : a novel - Curtis, Christopher Paul. (New York : Bantam Doubleday Dell Books for Young Readers, 1997)
The ordinary interactions and everyday routines of the Watsons, an African-American family living in Flint, Michigan, are drastically changed after they go to visit Grandma in Alabama in the summer of 1963.
"A Yearling book.".
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
Books for the Teen Age (NYPL), January 1998.
Child Study Children's Book Committee, January 1996.
Keywords: African Americans -- Fiction; Brothers and sisters -- Fiction; Family life -- Fiction; Historical fiction; Prejudices -- Fiction; African Americans -- Fiction; Family life -- Fiction; Historical fiction; Prejudices -- Fiction; Siblings -- Fiction; Birmingham (Ala.) -- Fiction; Flint (Mich.) -- Fiction; Birmingham (Ala.) -- Fiction; Flint (Mich.) -- Fiction